MAIN CHARACTER’S PERSONALITY ON “A CARIBBEAN MYSTERY” BY AGATHA CHRISTIE: JUNG-FREUD THEORY - Husnul Khotimah; Bambang Yulianto; Elisa Nurul Laili (BASIS (Bahasa dan Sastra Inggris), 2020)
Every human being has a different personality type. Personality is what makes humans look unique and not the same. There are many ways to analyze a person's personality, one of which is a psychological approach. The psychological theory of Carl Gustav Jung and Sigmund Freud is a way to analyze a person's personality types. The research method used in this study is a qualitative approach. Sources of research data is “A Caribbean Mystery” and the research data include: The Psychological types and Factor that influence the psychology of the main characters. Data collection techniques using library techniques, namely documents. Data analysis techniques using the techniques of reading, marking, coding and analysing. The result of this research can be formulated that on "A Caribbean Mystery" there are six personality types (Introversion-Thinking, Extroversion-Thinking, Introversion-Feeling, Extroversion-Feeling, Introversion-Sensing and Extroversion-Intuition), about the influencing factors of the psychological types is dominated by personal factors (Motive of Curiosity, Motive of Competence, Motive of Love, Motive of Self and The Need to Find Identity, Motive of Value, Motive of Self-fulfillment Needs, Attitudes, and Emotion.